From resilience to viability: a case study of indigenous communities of the North Rupununi, Guyana - Andrea Berardi; Céline Tschirhart; Jayalaxshmi Mistry; Elisa Bignante; Lakeram Haynes; Grace Albert; Ryan Benjamin; Rebecca Xavier; Deirdre Jafferally (EchoGéo)
'Resilience' is a term that has achieved significant prominence in scientific circles and now within popular discourse. However, its practical application is often unclear or confused because it can mean different things to different people: To resist? To adapt? To transform? In this paper, we propose a framework - System Viability - able to coherently engage with six distinct properties of all systems, from ecosystems to communities, allowing the identification of trade-offs and synergies for maximising the chances of systems persistence. We apply and evaluate the System Viability framework through participatory visual methods within three indigenous communities in the North Rupununi, Guyana. This paper highlights how the framework allows the measurement of community survival strategies in a consistent and theoretically corroborated way, with implications for national and international policy-makers aiming to promote resilience and sustainability.